2013
DOI: 10.1063/1.4811647
|View full text |Cite
|
Sign up to set email alerts
|

The impact of negative oxygen ion bombardment on electronic and structural properties of magnetron sputtered ZnO:Al films

Abstract: In order to study the impact of negative oxygen ion bombardment on the electronic transport properties of ZnO:Al films, a systematic magnetron sputtering study from ceramic targets with excitation frequencies from DC to 27 MHz, accompanied by strongly varying discharge voltages, has been performed. Higher plasma excitation frequencies significantly improve the transport properties of ZnO:Al films. The effect of the bombardment of the films by energetic particles (negative oxygen ions) can be explained by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…On the other hand, the intensity of the broad orange emissions centered at 650 and 750 nm, which are mainly related to deep-level emissions through oxygen interstitial, [44][45][46][47] decreases at a large x. This is because the flux of energetic negative oxygen ions, which cause the formation of oxygen interstitial in ZnO, 24 decreases with increasing x.…”
Section: With Buffer Layersmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the intensity of the broad orange emissions centered at 650 and 750 nm, which are mainly related to deep-level emissions through oxygen interstitial, [44][45][46][47] decreases at a large x. This is because the flux of energetic negative oxygen ions, which cause the formation of oxygen interstitial in ZnO, 24 decreases with increasing x.…”
Section: With Buffer Layersmentioning
confidence: 93%
“…In magnetron sputtering, there are many high-energy particles, such as negative oxygen ions and recoil Ar, which cause defect formation in ZnO films. 24,25 Since both particles are accelerated in the cathode sheath, 26,27 the flux of the energetic particles can be reduced by taking the off-axis configuration where the substrate is positioned out of the highenergy particles originating from the targets. Here, aiming at realizing high-quality ZnO films with a low defect density, the effects of off-axis configuration together with NMC buffer layers are investigated through the analysis of the properties of ZnO films fabricated at various substrate/target configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Tominaga et al [132] confirmed this effect for AZO films prepared by RF magnetron sputtering and related it to the bombardment of the film with negative oxygen ions coming from the target. This negative oxygen ion bombardment can introduce acceptor defects, such as oxygen interstitials into the growing film, and therefore decrease the charge carrier concentration as reported by Bikowski et al [9]. They observed a minimum in the resistivity for a certain substrate temperature that depends on the sputter method.…”
Section: Sputter Deposition Of Azo Thin Filmsmentioning
confidence: 76%
“…The bombardment of the growing film with negative oxygen ions is believed to cause the deactivation of charge carriers due to the formation of insulating secondary phases [8,9,63]. The formation of secondary phases has been reported to increase at high substrate temperatures due to the preferential desorption of Zn [63].…”
Section: Paper 2: Restoring the Properties Of Transparent Al-doped Znmentioning
confidence: 99%
See 1 more Smart Citation